Potency of Swallow Nest Extract (Collocalia fuciphago) as Pancreaprotector Through Oxidative Mechanism in Rats (Rattus norvegicus) Induced by Streptozotocin - Agnes Frethernety; Satriyandi M; Francisca Diana Alexandra (Berkala Kedokteran, 2018)
Abstract: Diabetes mellitus is a clinical syndrome with characteristics of hyperglycemia. Hyperglycemia can lead to the formation of excessive free radical compounds that trigger oxidative stress, especially on pancreatic β cells. Swallow nest contains amino acids which are insulin-forming compounds and glutathione that can act as a major reducing agent and antioxidant defense. The purpose of this study is to analyze the effect of swallow’s nest water extract as a pancreaprotector through oxidative mechanism in rats (Rattus norvegicus) induced by streptozotocin. The rats induced by streptozotocin at a dose of 40 mg/kg BW and then randomly divided into 4 groups. Control groups were given aquades and 3 treatment groups, respectively were administered swallow’s nest water extract at doses of 1, 10, 100 mg/kg BW for 21 days. Fasting blood glucose levels were measured on 7, 14 and 21 day. MDA measured after  the animal is determined  at day 28th.Level of  fasting blood glucose and MDA were analyzed by statistic using Kruskal Wallis test followed by multiple comparisons Mann Whitney test. There was a significant decrease in fasting blood glucose level with p = 0.04 in all treatment groups compared the control group. The administration of swallow nest extract significantly decreased MDA pancreas with p value = 0.000 and dose 100 mg/kgBW extract of swallow’s nest significantly decrease pancreatic MDA level. The administration of swallow’s nest water extract shows decrease of fasting blood sugar and has a protective effect on the rats’ pancreas  through oxidative mechanism. Keywords: Swallow's nest extract, MDA